The effect of sulforaphane on markers of inflammation and metabolism in virally suppressed HIV patients - Giron, Jose; Smiarowski, Lauren; Katz, Johannah (Frontiers in Nutrition, 2024)
There are currently 1.2 million people living with HIV (Human Immunodeficiency Virus) in the United States. Virally suppressed HIV patients commonly experience chronic inflammation which increases the risk for other chronic conditions. This inflammation can be quantified with a variety of biomarkers. Some current antiretroviral compounds bring about metabolic abnormalities and promote weight gain often associated with increases in visceral adipose tissue (VAT) and an increase in the risk of diabetes mellitus and cardiovascular disease. Sulforaphane, an isothiocyanate found in cruciferous vegetables, has shown efficacy in animal models by reducing lipid levels, lowering inflammatory markers, and decreasing fat mass. A double-blind randomized controlled pilot study with 14 virally suppressed HIV patients was conducted to evaluate the effects of 40 mg (225 µmol) of sulforaphane, once daily, over 12 weeks, followed by a 4-week washout period. There was a significant decrease in C-reactive protein compared to the control group (p = 0.019). Sulforaphane has been studied in a multitude of conditions and diseases, but this is the first study in a human population of patients living with HIV.